Insights into crack prevention and property improvement for additively manufactured ultra-high-strength steel structures with complex geometries - Jun Wang; Mark Taylor; Chenglei Diao; Ed Pickering; Jian Qin; Yao Lu; Sonia Martins Meco; Jialuo Ding; Stewart Williams (Additive Manufacturing Letters)
Hybrid wire-arc directed energy deposition (WDED), in which complex features are deposited onto a forged base, offers a cost-effective solution for manufacturing geometrically complex ultra-high-strength steel components, particularly for aerospace applications. However, cracking at the base forging/build interface during post-build heat treatment limits its widespread application. This study investigates the underlying causes of interfacial cracking, highlighting microstructural inhomogeneity, elemental segregation and transformation stresses as likely key contributing factors. A modified three-step post-build heat treatment incorporating a normalisation step was developed to mitigate some of these issues. The optimised process successfully suppressed cracking by refining prior-austenite grains before the application of a conventional quenching step. This enhanced tensile performance beyond AMS6419K standards, supporting the industrial implementation of hybrid WDED in aerospace structures.